Analysis of the Influence of Economic Growth on Poverty Levels in Medan City - Apen Salomo Silalahi; Aisyah Harningtias; Mutiara Rengganis (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of economic growth on the poverty rate in Medan City in 2011 - 2020. This research uses a quantitative approach. The research location is in the city of Medan. The method used in this study is a simple regression test with SPSS with Economic Growth as the independent variable (X) and Poverty Level as the dependent variable (Y). The results of the research show that the economic growth that occurred in the city of Medan has a significant positive effect on the level of poverty in the city of Medan. Therefore, it is necessary to make efforts to increase economic growth in the city of Medan in order to reduce the level of poverty in the region.